Effect of Tillage, Irrigation, and Nutrient Levels on Growth and Yield of Sweet Potato in Rice Fallow. (22nd December 2011) - Nedunchezhiyan, M.; Byju, G.; Ray, R. C.
Abstract : A field experiment was conducted during the year 2007-2008 and 2008-2009 in Bhubaneswar, India to study the effect of tillage, irrigation and nutrient levels on growth and yield of sweet potato ( Ipomoea batatas L.) in rice fallow. The results revealed that the conventional tillage system of sweet potato planting recorded maximum fresh root yield. During the year 2007-2008 and 2008-2009, the fresh root yield in this system was 4.6% and 30.3% higher than the minimum tillage treatment, respectively. Similarly 5.6% and 21.7% higher green fodder yields were obtained in conventional tillage compared to minimum tillage treatment during the year 2007-2008 and 2008-2009, respectively. But lower consumptive use and water use efficiency (WUE) were observed in conventional tillage than minimum tillage. Increasing irrigation and nutrient levels increased root and fodder yield significantly in both the years as well as reduced the soil compactness. The consumptive use and WUE were decreased with increasing irrigation levels, and increased with increasing levels of nutrients. Minimum tillage has advanced planting of sweet potato 15 to 17 days and produced 80–90% root and fodder yield of conventional tillage.